Rethinking foreign policy analysis states, leaders, and the microfoundations of behavioral international relations - edited by Stephen G. Walker (New York Routledge, 2011)
Stephen G. Walker, Akan Malici, and Mark Schafer present a definitive, social-psychological approach to integrating theories of foreign policy analysis and international relations―addressing the agent-centered, micro-political study of decisions by leaders and the structure-oriented, macro-political study of state interactions as a complex adaptive system. The links between the internal world of beliefs and the external world of events provide the strategic setting in which states collide and leaders decide.
Includes bibliographical references (p. [290]-317) and index.
Keywords: International relations--Decision making